The warrior heir - Chima, Cinda Williams (New York : Hyperion Paperbacks, 2007)
Sixteen-year-old Jack discovers that he is one of the last warriors of the Weirlind, an underground society of magical people, and must fight to determine which house--the White Rose or the Red Rose--will rule the Weir.
Young Adult
Young Adult
School Library Journal
Bulletin of the Center for Children's Books starre
Horn Book
Keywords: Magic -- Fiction; Wizards -- Fiction; Identity -- Fiction; Fantasy; Magic -- Fiction; Wizards -- Fiction; Individuality -- Fiction; Fantasy fiction